Wspólnota komunikatywna militarna odzwierciedlona w modlitewniku "Przyjaciel żołnierza. Modlitewnik dla żołnierzy wyznania prawosławnego" z 1937 r. - rekonesans badawczy = The military communicative community reflected in the prayer book "A Soldier`s Friend. A prayer book for soldiers of the Orthodox faith" from 1937 - research reconnaissance - Zotova, Nataliia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The presented article has been devoted to the study of the specificity of communicative communities recorded in the prayer book "Przyjaciel żołnierza. Modlitewnik dla żołnierzy wyznania prawosławnego" ("Friend of the Soldier. Prayer book for Orthodox soldiers") (1937). On the basis of the selected text, an attempt was made to study the functioning of the military and religious communicative community and various ethnic communities in the Eastern Borderlands during the Second Polish Republic. Relations in these communities and between them, communicative needs against the backdrop of socio-political changes, institutions leading the communities and activists who played an important role in the publication of the Orthodox prayer book were described.
Keywords: wspólnota komunikatywna; modlitewnik prawosławny; kościół prawosławny; autokefalia; II Rzeczpospolita; polonizacja; wojsko polskie; żołnierz; duszpasterstwo wojskowe; communicative community; Orthodox prayer book; Orthodox Church; autocephaly; Second Polish Republic; polonization; Polish Army; soldier; military chaplaincy